Reading History into Law: Who Is Worthy of Reparations? Observations on Spain and Portugal's Return Laws and the Implications for Reparations. Issue 1 (1st October 2017) - Jinan Bastaki
Abstract : In 2015, both Portugal and Spain passed similar laws offering Sephardic Jews their respective citizenships to redress the historic wrong of their persecution and expulsion under the Inquisition. Portugal and Spain are now the only other countries in the world to have a return law for the Jewish people, in addition to Israel—albeit limited to Sephardic Jews. Given the underlying reasons for the passing of this law, it is notable that Iberian Muslims, who were also expelled, have no recourse for redress—not even symbolically. While remedies can be limited under international law, this article explores the relationship between the historical narrative of the Arab/Muslim occupiers, the current popular portrayal of Muslims in the Iberian Peninsula, and the relationship between the absence of reparations and current discrimination against groups.